Non-lactational Infectious Mastitis in the Americas: A Systematic Review - Costa Morais Oliveira, Victor; Cubas-Vega, Nadia; López Del-Tejo, Paola; Baía-da-Silva, Djane C.; Araújo Tavares, Michel; Picinin Safe, Izabella; Cordeiro-Santos, Marcelo; Lacerda, Marcus Vinícius Guimarães; Val, Fernando (Frontiers in Medicine, 2021)
Background: Non-lactational infectious mastitis (NLIM) is an inflammatory breast disease with broad clinical presentation. Inadequate treatment can lead to chronic infections that cause breast deformities. NLIM information is limited, especially in the Americas. A systematic review and meta-analysis have been conducted here. Methods: A literature search was conducted in three databases (Lilacs, PubMed, and Scielo) on NLIM cases in the Americas. Demographic, epidemiological, clinical, radiological, and laboratory data were extracted. The main characteristics and results were also compared according to the country's gross national income. Results: A total of 47 articles were included, resulting in 93 cases. The etiological agent was described in 86 (92.5%) patients. Bacteria were the most prevalent etiology (73; 84.8%). Amongst bacterial diagnoses, more frequent cases were Mycobacterium tuberculosis (28; 38.4%); Corynebacterium spp. (15; 20.5%); non-tuberculous mycobacteria (13; 17.8%). The cases were reported in eight different countries, with the USA being the country with the highest number of cases (35; 37.6%). Patients from high-income countries group presented a shorter diagnostic time when compared to low, low-middle, and upper-middle-income countries. A greater number of radiographic studies with pathological findings were described in high-income countries. Conclusion: Non-lactational infectious mastitis is a complex public health problem with diagnostic and treatment challenges. Hence, multi-professional approach-based additional studies are recommended on its epidemiology, diagnosis, treatment, and control.